Determination of trajectories of metallic spheres settling in non-newtonian fluids - Lichti, D.; Gumulya, Monica; Horsley, R. (Wiley-Blackwell Publishing, 2009)
A "videogrammetric" system to measure the trajectory of small metallic spheres falling through a slurry-filled tank has been developed to support fluid dynamics research. The system used two low-cost video cameras and a combination of commercially available and custom-built software for the image acquisition, the measurement and tracking of the spheres in the imagery and the photogrammetric operations. After a review of relevant literature and a description of the system, this paper reports on an extensive testing regime conducted to gauge the performance of the system. The results show that it achieved object space coordinate precision and accuracy better than the required figure of 1 mm. Simulation-based analyses, to quantify the sensitivity of refraction corrections in object space to the accuracy of the three refractive indices and distance parameters involved in the system, are also reported. The results of these tests demonstrated that some parameters need only be specified to about 56% of their true value whereas others must be accurate to better than 2%. Finally, results from two examples in sphere trajectory determination are presented and analysed. © Journal Compilation © 2009 Remote Sensing and Photogrammetry Society and Blackwell Publishing Ltd.